The effectiveness of using the penta Gram strategy in the achievement of mathematics among fifth-grade students (Journal of the College of Basic Education, 2022)
The aim of the research is to identify (the effectiveness of using the penta Gram strategy in mathematics achievement among fifth-grade students) The number of the sample members reached (58) students, of which (29) students were for the control group, and (29) students were for the experimental group. The researchers chose the experimental method and one of the partial control designs for the two equivalent groups (experimental and control) with the pre and post test, and the researcher also prepared an achievement test consisting of (35) objective items of the type of multiple choice with four alternatives and the validity was verified. The researchers used the Keoder-Richardson equation (k-R20) to calculate the test stability factor, and the t-test was used for two independent samples to process the data using the statistical program (SPSS).The following result was reached: There is a statistically significant difference between the mean scores of the two research groups in the achievement test and in favor of the experimental group, which studied the subject matter specified for the duration of the experiment using the Penta Gram strategy on female students of the control group who studied in the usual way of teaching, and in light of this result, the null hypothesis is rejected